Open feedback in gymnastic judging causes conformity bias based on informational influencing - Boen, F.; van Hoye, K.; Vanden Auweele, Y.; Feys, J.; Smits, T. (Journal of Sports Sciences, 2008)
The aims of this study were twofold: (1) to determine whether open feedback (i.e. the ability to hear or see the scores of colleague judges after each performance) would lead judges in gymnastics to conform with their colleagues, and (2) to identify the underlying process on which this conformity is based. Twenty-three certified Flemish judges in women's gymnastics were randomly divided into panels of a maximum of five judges. These panels had to rate the same 30 videotaped individual vaults: 15 in phase 1 and 15 in phase 2. Two independent variables were orthogonally manipulated: feedback (or no feedback) during phase 1 and feedback (or no feedback) during phase 2. The results of phase 1 revealed that the variation between the judges' scores was less within panels that had received feedback than within panels that had not received feedback. We therefore conclude that the availability of feedback elicits conformity among gymnastic judges. The results of phase 2 indicated that this conformity continued even when feedback was no longer provided, suggesting that the observed conformity was based on informational influencing (i.e. because of uncertainty about the correct responses) and not on normative influencing (i.e. out of fear of standing out in the group).